2002
DOI: 10.1117/12.453837
|View full text |Cite
|
Sign up to set email alerts
|

Cramer-Rao bound analysis of wideband source localization and DOA estimation

Abstract: Downloaded From: http://proceedings.spiedigitallibrary.org/ on 07/02/2015 Terms of Use: http://spiedl.org/terms Proc. of SPIE Vol. 4791 311 Downloaded From: http://proceedings.spiedigitallibrary.org/ on 07/02/2015 Terms of Use: http://spiedl.org/terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…From (18), we see that is zero for all if and only if , which is equivalent to with . In [1], it is shown that is zero for uniform circular arrays. With Theorem 1, we extend this result to all isotropic arrays, and we also show that isotropy is a necessary and sufficient condition.…”
Section: A Planar Arraysmentioning
confidence: 99%
See 4 more Smart Citations
“…From (18), we see that is zero for all if and only if , which is equivalent to with . In [1], it is shown that is zero for uniform circular arrays. With Theorem 1, we extend this result to all isotropic arrays, and we also show that isotropy is a necessary and sufficient condition.…”
Section: A Planar Arraysmentioning
confidence: 99%
“…Since are independent samples of a zero-mean Gaussian process, the Fisher information matrix (FIM) on the the parameter vector is given by (see also [1], [3], and [4])…”
Section: A Planar Arraysmentioning
confidence: 99%
See 3 more Smart Citations